2023
DOI: 10.47115/bsagriculture.1193712
|View full text |Cite
|
Sign up to set email alerts
|

Geometric Morphometric Investigation of Incus in Horse (Equus ferus caballus) and Donkey (Equus Asinus)

Abstract: In this study, it was aimed to determine the shape of the incus in horse and donkey by geometric morphometric method and to evaluate the shape differences between horse’s and donkey’s incus. The left incus bone of 5 adult horses and 5 donkeys were used in the study. Incus were photographed at same lateral direction. Thirteen homologous landmarks were marked from the photographs using TpsUtil (Version 1.79) and TpsDig2 (Version 2.31) software. As a result of the study, the first principal component explained 38… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(1 citation statement)
references
References 13 publications
0
1
0
Order By: Relevance
“…One study examined the shape variations of the incus and the differences between the donkey and the horse. The results reported that the corpus incudis edges (right, left, and bottom) were flatter in donkeys [ 48 ]. The study revealed that taxonomy was possible for ear ossicles using the geometric analysis method.…”
Section: Discussionmentioning
confidence: 99%
“…One study examined the shape variations of the incus and the differences between the donkey and the horse. The results reported that the corpus incudis edges (right, left, and bottom) were flatter in donkeys [ 48 ]. The study revealed that taxonomy was possible for ear ossicles using the geometric analysis method.…”
Section: Discussionmentioning
confidence: 99%